SHERPA TRACK DIPLOMASI ANTI KORUPSI DALAM G20 PADA PEMERINTAHAN JOKO WIDODO - Nur, Siti Fauziyah; Saeri, Mhd. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The G20 is the largest cooperation forum that consists of 19 countries and 1 European Union. 2022 is the year when Indonesia has the opportunity to become the G20 presidency. The G20 is believed to be a very strategic international community where more than 60% of the world's population, 75% of global trade, and 80% of GDP are members. world, 75% of global trade, and 80% of the world's GDP (Gross Domestic Product). Corruption, which is one of the focuses of discussion within the G20 itself, led to the establishment of the Anti Corruption Working Group (ACWG) as an effort to raise the standards of transparency, accountability and the G20's contribution to the global fight against corruption. Corruption is the second most urgent problem to be solved after employment. In 2021, the achievement of the Corruption Perception Index (CPI) in Indonesia is 38 on a scale of 0-100. By using a Neorealist perspective, we can see in terms of Indonesia as a middle power country, which in this case will show its strength through multilateral cooperation in the form of the G20. Regarding the specificity of the discussion that will be focused on the eradication of corruption through the ACWG Working Group. Where the eradication of corruption itself is an important thing to be discussed with the aim of being able to build productive synergy, through educational strategies to internalize anti-corruption values to all elements of society. On the other hand, the big role held by Indonesia should be a big breakthrough for all the results of decisions at the G20. On the one hand, the implementation efforts of the Indonesian government related to the ACWG agreement will affect the results of the Corruption Perception Index in Indonesia. How the country is present to be able to carry out the results of the discussion will be explained clearly. Keywords: G20, Corruption, Indonesian Government